6m+10=8m

Simple and best practice solution for 6m+10=8m equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6m+10=8m equation:


Simplifying
6m + 10 = 8m

Reorder the terms:
10 + 6m = 8m

Solving
10 + 6m = 8m

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-8m' to each side of the equation.
10 + 6m + -8m = 8m + -8m

Combine like terms: 6m + -8m = -2m
10 + -2m = 8m + -8m

Combine like terms: 8m + -8m = 0
10 + -2m = 0

Add '-10' to each side of the equation.
10 + -10 + -2m = 0 + -10

Combine like terms: 10 + -10 = 0
0 + -2m = 0 + -10
-2m = 0 + -10

Combine like terms: 0 + -10 = -10
-2m = -10

Divide each side by '-2'.
m = 5

Simplifying
m = 5

See similar equations:

| 7x+4(-3x)(-12)=8 | | -10k+20=13k-18-8 | | 16(6x-24)=x-4 | | 11x-5=6x+25 | | 3g+3W=300 | | 24-4x=3(x+1) | | 65=5(4x+1) | | 7p-4+12p=-15+3p | | 8w+4=8w | | 8x^2-4x= | | P=2-2q | | 52=w-8 | | -11+9t=11-4t+17 | | 3y+y+20=7y+20-5y | | 4K-23=-5(7k-11) | | 4(3-x)+5(x-6)=x | | 6p-5+7p=47 | | 6a-3(a+2)=1/2(a+8) | | 16p-4=-15 | | 4K-23=-5(7k+11) | | 2c+(3c-4)=5c-4 | | -2w-18w-9=-18w+5 | | 7c-4=31 | | 18-6a=-1a-12 | | 0.3c=6 | | 6F=60 | | 2c+(3c-4)=4c-4 | | 1/2(x-2)=3x-6 | | 2a-3b=-10forb | | x-14-(2x+5)=0 | | 14-15s=-16s | | 3b-4+b-9= |

Equations solver categories